Devastating neurological complication after pectus excavatum surgery - Pavol Omanik; Miroslava Funakova; Jozef Babala; Igor Beder (Elsevier, 2023)
Adverse reactions and complications in connection with mini-invasive pectus excavatum correction can range from minor to life-threatening. The authors present a unique case of a patient who developed a severe neurological deficit after a mini-invasive correction of the pectus excavatum.A 16-year-old patient with symptomatic pectus excavatum, and a compression of the right atrium and ventricle verified by cardiac workup, was indicated for the Nuss correction. A mini-invasive surgery was performed under general anesthesia with epidural analgesia, without complications. On the first postoperative day, a weak triparesis developed, affecting both the lower limbs and the left upper limb. An immediate MRI revealed a multisegmented acute transverse myelopathy ranging from C1 to T11, with maximal cervical involvement, without intraspinal hemorrhage. An intravenous combination of antibiotics, virostatics, and corticosteroids was used in the acute phase of treatment. Both infectious and autoimmune etiology were ruled out by diagnostic lumbar puncture. The patient's neurological status has gradually improved during intensive physiotherapy in a specialized center: 12 months later, the patient can walk with support, but continues to experience micturition problems. A follow-up MRI showed a significant regression of signal changes as well as a spinal cord edema, reduced to the C5 - T2 range.